Power supply devices for auxiliary blood circulation - F. R. Ismagilov; V. E. Vavilov; R. A. Nurgalieva; A. Kh. Miniyarov (Омский научный вестник)
The article discusses issues, problems and methods for solving them related to the transfer of energy to transplanted assisted circulation devices, which allow for efficient, safe and stable energy transfer. One of the promising methods of energy transfer is wireless energy transfer, which allows patients with implantable devices to lead a more active life, avoiding infection and rejection of the devices.